Clinical and microbiological factors predicting outcomes of nonfermenting gram-negative bacilli peritonitis in peritoneal dialysis - dos Santos, Ana Claudia Moro Lima [UNESP]; Hernandes, Rodrigo Tavanelli [UNESP]; Montelli, Augusto Cezar [UNESP]; Monteiro, Aydir Cecília Marinho [UNESP]; Barbosa, Thais Alves [UNESP]; Camargo, Carlos Henrique; Ferreira, Adriano Martison [UNESP]; Mondelli, Alessandro Lia [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP]; Barretti, Pasqual [UNESP] (Springer Nature, 2021)
Peritonitis due to gram-negative bacilli (GNB), particularly nonfermenting GNB (NF-GNB), is a serious complication of peritoneal dialysis with a low resolution rate. Beyond the patient’s condition, microbiological properties such as antimicrobial resistance, biofilm production and other virulence factors can explain the poor outcomes. This study aimed to evaluate the influence of patient condition, microbiological characteristics, including biofilm production, and treatment on peritonitis outcome. We reviewed the records of 62 index episodes caused by NF-GNB that occurred between 1997 and 2015 in our center. The etiologies were species of Pseudomonas (51.6%), Acinetobacter (32.2%), and other NF-GNB (16.1%). There was a high (72.9%) proportion of biofilm producer lineages. The in vitro susceptibility rate of Pseudomonas spp. to amikacin, ciprofloxacin, and ceftazidime was significantly greater than that of Acinetobacter spp. and other species; however, there was a similar low resolution rate (< 45%) among the episodes attributable to them. Preexisting exit-site infection was independently associated with nonresolution. No other factor, including biofilm production, was associated with the outcome. The higher in vitro susceptibility of Pseudomonas compared to other NF-GNB that presented a similar resolution rate suggests that bacterial virulence factors such as biofilms can act in concert, thereby worsening the outcome.